PERKEMBANGAN SUASANA POLITIK MUSLIM DI XINJIANG, CHINA: SATU TINJAUN UMUM DARI PERSPEKTIF SEJARAH PERADABAN - Jais, Abd Wahid; Kassim, Faezah (Journal of Al-Tamaddun, 2005)
The Muslint conlnlLutit'- in China proctices different cLiltltre uttl way oJ life compare(l to the other ethics in Chirta. Thet have nlade nwnerous contributions for the fornrfiiott and clevelopment of Chinese civiLization ond generolL,', tltey are well acceptetl in the Chinese commtnimn, However, Mtrslim contmmti\, in lhe province o.t'' Xiniicutg is enduring, o clifferent situation cts for centuries they are ertcotrttterittg political crisis with the Chinese governnTent. This orticle r/rscasses their political conclition based on the historicol civilizational perspective ever since the orrivcLl o.f IsLam until the existence of communism in Chino. Factors of Xinjiang Muslim's resistance ogoinst the governmertt, tt,hich highlights Xinjiang Mttslirn's determinism to continue fighting until the dignity of their religion, race and provirtce been reinstatecl, are also elctboroted.